UPAYA MENINGKATKAN HASIL BELAJAR SISWA PELAJARAN BIOLOGI PEWARISAN SIFAT MELALUI MODEL PEMBELAJARAN JIGSAW - Dewi Widianingsih (Pedagogia: Jurnal Ilmiah Pendidikan, 2020)
EFFORTS TO INCREASE THE RESULT OF STUDENTS LEARNING OF BIOLOGY THE NATURE OF THE HEIR TROUGH LEARNING MODEL JIGSAWThis study moved from the phenomenon happened in the classroom that the low understanding and the results of students learning on Biology about regulation system. Therefore a theacher need to consider the learning model jigsaw so it can be increasing the activity and the results of students learning.This study aimsto (1) determine the learning outcomes of students in Biology about regulation system through the learning model of jigsaw so that it can improve the activity and learning outcomes students of XII IPA 2 SMAN 9 Bogor 2018/2019,(2) Knowing the process of improving students learning outcomes of Biology through jigsaw of XII IPA 2 SMA N 9 Bogor in the first semester 2018/2019, (3) measure the increasing in student learning outcome in Biology about regulation system through a learning model “jigsaw”. The results of this study show that by using the learning model “jigsaw” can be a variety of fun learning for students so that it can prove to increase students learning outcomes. Before using tes learning model “jigsaw” learning outcomes of students reached only 65,65, then increase after using jigsaw to 75 in cycle 1 and 81,72 on sycle 2. From the description above, the researcher concluded that learning model “jigsaw” matched to the learning material can create fun learning situation to increase students learning outcomes.